Well posedness and stability result for a thermoelastic laminated Timoshenko beam with distributed delay term - Hassane, Doha Ihssane; Yazid, Fares, Directeur de thèse; Djeradi, Fatima Siham, Directeur de thèse (Laghouat : Université Amar Telidji - Département de mathématiques, 2024)
In this memory , we considered a linear thermoelastic laminated Timoshenko beam with distributed delay, where the heat conduction is given by Cattaneo’s law. we established the global existence and the uniqueness of the solution by using the semi-group theory. Finally, we studied the asymptotic behavior of solution by using the multiplier method, and we proved the exponential an the polynomial stabilities of the system for the cases of equal and non-equal speeds of wave propagation.